Split anode calorimetry of low current TIG arcs. - Egerland, Stephan Alfred (Cranfield University, 2019)
Various techniques have been used to understand the distribution of energy within a Tungsten Inert Gas (TIG) Welding arc. Spectroscopy, electrostatic probe measurement, split anode calorimetry, as well as advanced numerical modelling techniques to a varying degree have found their application in scientific research - deployed to improve the comprehension of phenomena observed in TIG arcs interacting with the parent material to join. While spectroscopic methods have the advantage of being able to determine arc energy density variations as a function of the temperature of electrons and other charged species in the plasma, it is difficult to determine the power or heat flux arriving at the anode or workpiece. The electrostatic probe technique, conversely to spectroscopy, is reckoned among the invasive methods in arc plasma investigations. That is, the subject of investigation is, to considerable degree, affected in its structure by interacting with the biased probe wires transferred through the plasma plume which may finally lead to substantial deviations from the real conditions actually present inside the arc. Numerical modelling, which is based on assumptions simplifying the real arc plasma conditions to a certain degree, still require the empirical experiment for validation of the results achieved by the model. Finally either the measurement of radial arc pressure as an equivalent of the energy content of the arc, or deploying split anode calorimetry are the most appropriate methods, while the latter was found simpler to implement versus the former. Instead of a workpiece material which is normally used for welding applications, two water cooled copper anodes which are not melted by the welding arc are applied. As the welding torch is traversed across the interface between the two anodes the current and voltage owing through each anode half is measured. As an additional benefit of split anode calorimetry the electrical arc power - achievable by multiplying the transient values of electrical current by the voltage correspondingly measured - and the calorimetric power or heat flux to the anodes can be measured. All aforementioned scientific approaches, however, require the involvement of partly complex numerical methods, since it appears impossible to directly derive the targeted information. This again may serve in part as a considerable source of error in the final output which can lead to significant variations while investigating welding arcs of similar appearance. This study aims at deploying split anode calorimetry but pairing the investigation of low current TIG arcs with the assessment of how the shielding gas nozzle design may affect the radial energy density of the arcs applied. Besides fundamental information on the mere distribution profile of low current TIG welding arcs and answering the question whether a regularly postulated Gaussian-like distribution applies, the involvement of different nozzle diameters was targeting at also deriving valuable information for the welding practitioner deploying TIG welding as an industrial joining process. It could be shown that phenomena were observed through the investigation which have not been reported so far in the literature, however were found to partly considerably affect the final output of the measurement and hence also influence the degree of significance of the results achieved. In TIG welding arc investigation split anode calorimetry is found comparably favoured over other methods because of its reasonable experimental set up and deriving robust and meaningful output from the measurement. It was thus scientifically attempted to achieve quantitative explanations for the phenomena occurring; to provide future researchers with information seriously to be taken into account when intending to apply split anode calorimetry for TIG welding arc analyses
Keywords: energy distribution; welding; technique; modelling; copper anodes; numerical